2014
DOI: 10.5664/jcsm.3612
|View full text |Cite
|
Sign up to set email alerts
|

High Hypopnea/Apnea Ratio (HAR) in Extreme Obesity

Abstract: Study Objectives:The study was performed to evaluate the hypothesis that the extremely obese manifest sleep disordered breathing with a preponderance of hypopneas and relative paucity of obstructive apneas. Methods: Retrospective review of 90 adults with obstructive sleep apnea-hypopnea syndrome (OSAHS) matched for age and gender, comparing two groups, Group A: body mass index (BMI) < 35, Group B: BMI ≥ 45. Exclusion criteria: age < 18 years, pregnancy, ≥ 5 central apneas/hour, BMI ≥ 35 < 45. Primary Outcome M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 16 publications
(18 reference statements)
1
14
1
Order By: Relevance
“…24 In contrast, the occurrence of hypopneas is more dependent on upstream resistance, 24 which may indicate different mechanisms behind the pathogenesis of apneas and hypopneas. 23 In addition, increased genioglossal fatigability has been reported in non-obese OSA patients, whereas, in obese OSA patients, the performance of the genioglossus muscle did not differ from that of obese controls not having OSA. 25 Therefore, it can be speculated that, if obese patients with OSA have better performance of genioglossus muscle compared with patients with OSA and who are not obese, this could lead to a higher occurrence of hypopneas and reduce the number of apneas.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…24 In contrast, the occurrence of hypopneas is more dependent on upstream resistance, 24 which may indicate different mechanisms behind the pathogenesis of apneas and hypopneas. 23 In addition, increased genioglossal fatigability has been reported in non-obese OSA patients, whereas, in obese OSA patients, the performance of the genioglossus muscle did not differ from that of obese controls not having OSA. 25 Therefore, it can be speculated that, if obese patients with OSA have better performance of genioglossus muscle compared with patients with OSA and who are not obese, this could lead to a higher occurrence of hypopneas and reduce the number of apneas.…”
Section: Discussionmentioning
confidence: 92%
“…These findings are in line with a previous study in which very obese (BMI Ն 45 kg/m 2 ) OSA patients were compared with OSA patients having a BMI Ͻ35 kg/m 2 . 23 It has been reported that the minimum intraluminal airway pressure that is needed to keep the upper airway open is one of the most important factors in the pathogenesis of apneas. 24 In contrast, the occurrence of hypopneas is more dependent on upstream resistance, 24 which may indicate different mechanisms behind the pathogenesis of apneas and hypopneas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective study of 90 adults with OSA, comparing two groups with body mass indices (BMI) ≥45 vs. BMI < 35, matched for age and gender, the hypopnea-toapnea ratio (HAR) was significantly higher in the BMI ≥45 group (38.8 ± 50.7) compared to the BMI < 35 group (10.6 ± 16.5), p = 0.0006. (Mathew & Castriotta, 2014) The hypopnea index, but not the apnea index, was also higher in the BMI ≥45 vs. BMI < 35 group (28.7 ± 28.6 vs 12.6 ± 8.4, p = 0.0005), as was the AHI (35.5 ± 33.8 vs 22 ± 23, p = 0.03). In addition, the end-tidal CO2 was higher in the higher BMI group.…”
Section: I) Effect Of Bmimentioning
confidence: 80%
“…However, the hypopnea-to-apnea ratio did not appear to be influenced by the presence or absence of hypoventilation and was similar for those with or without obesity hypoventilation syndrome. (Mathew & Castriotta, 2014) In fact, BMI was the only significant predictor of HAR (adjusted r2 = 0.138; p = 0.002) when adjusting for age, gender, race, and ETCO2. Of note, a small sample size may have confounded the study findings.…”
Section: I) Effect Of Bmimentioning
confidence: 89%